Viet Nam - a Transition Tiger? - Arkadie, Brian Van (ANU Press, 2004)
Viet Nam has seen consistent rapid economic growth and impressive declines in poverty since it initiated its Doi Moi economic reforms in the late 1980s. Viet Nam has taken a selective, step-by-step approach to reform-an approach often criticised by proponents of the Washington Consensus. That this approach has been so successful has come as something of a surprise to much of the international community. Analysing closely aspects of Viet Nam's reform process, enterprise development, income growth and poverty alleviation, Viet Nam: a transition tiger? argues that Viet Nam's remarkable development is not readily explained by the more orthodox versions of the Washington Consensus. Successful policy is not built on mechanistic replication of some general reform blueprint, but on responding pragmatically to specific national circumstances. Government policy has had an impact on economic performance but economic experience has also guided the formulation of economic policy. Faced with increasingly complex economic conditions, Vietnamese policymakers will need to rely more than ever on their flexibility and pragmatism if Viet Nam's remarkable economic performance is to be sustained.